2019
DOI: 10.3389/fimmu.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory T Cell in Active Systemic Lupus Erythematosus Patients: A Systemic Review and Meta-Analysis

Abstract: Background: Regulatory T cells (Tregs) researches in systemic lupus erythematosus (SLE) have floundered over the years, reports on the numbers and function of Tregs in SLE present quite contradictory results. We therefore conducted a meta-analysis to verify the changes of Tregs in active SLE. Methods: We systematically searched PubMed, Embase, and ISI web of knowledge databases for eligible articles. In total, 628 active SLE patients and 601 controls from 18 studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 62 publications
0
47
0
Order By: Relevance
“…Anyway, we observed a significant decrease in the percentage of Tregs in our population. This could reflect the initial steps to tolerance breakdown, as a decrease in the frequency or number of Tregs has been associated with AID, such as SLE (28, 29), systemic sclerosis (2527) or rheumatoid arthritis (3032). In AAV patients, unlike other AID, an increased proportion of Tregs has rather been reported (36) but with impaired properties (37).…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, we observed a significant decrease in the percentage of Tregs in our population. This could reflect the initial steps to tolerance breakdown, as a decrease in the frequency or number of Tregs has been associated with AID, such as SLE (28, 29), systemic sclerosis (2527) or rheumatoid arthritis (3032). In AAV patients, unlike other AID, an increased proportion of Tregs has rather been reported (36) but with impaired properties (37).…”
Section: Discussionmentioning
confidence: 99%
“…The past decade has seen intense interest in evaluating the clinical utility of Tregs for a variety of indications including hematopoietic stem cell transplantation, autoimmune diseases and solid organ transplantation [3,27]. While the results from these initial clinical trials have demonstrated the potential therapeutic value of Tregs, isolation and expansion of Tregs is a major challenge due to reduced Treg frequencies and/or functionally defective Tregs reported in patients with autoimmune disorders [28][29][30][31][32][33][34]. In order to overcome this deficiency, a variety of ex vivo strategies have been developed to select, isolate and expand Tregs [4].…”
Section: Discussionmentioning
confidence: 99%
“…The development of SLE is dependent on a complex interplay between genetic, environmental, and immunological factors ( 85 , 86 ). Among these, defective function of regulatory T cells and polyclonal activation of B lymphocytes leading to the production of auto-antibodies seems to play a major role ( 87 89 ).…”
Section: Hla-g-expressing Immune Cells In Autoimmune Diseasesmentioning
confidence: 99%